Preliminary Human Radiation Dose Estimates of PET Renal Agents, Para-18F-Fluorohippuric Acid and Ortho-124I-Iodohippuric Acid from Rat Biodistribution Data - Cheki, Mohsen; Papie, Maryam; Mansi, Luigi; Kitson, Sean; Gali, Hariprasad (Current Radiopharmaceuticals, 2018)
Background: Para-18F-fluorohippuric acid (18F-PFH) and ortho-124I-iodohippuric acid (124IOIH) were recently identified as potential radiotracers suitable for conducting renography using positron emission tomography (PET). The aim of this work was to estimate preliminary human-equivalent internal radiation dose of 18F-PFH and 124I-OIH using the biodistribution data reported in healthy rats. The results were compared with the absorbed dose data of technetium-99m-mercaptoacetyltriglycine (99mTc- MAG3) as documented in the International Commission on Radiological Protection (ICRP) publication 80. Methods: The medical internal radiation dose (MIRD) formula was applied to extrapolate data from rats to human and to project the absorbed radiation dose for various organs in humans. S factor was calculated by Monte-Carlo N-particle (MCNP) simulation. Results: Our dose prediction shows that an injection of 18F-PFH or 124I-OIH in humans would result in an estimated effective absorbed dose of 0.09 or 0.17 μSv/MBq respectively for whole body, which is about 135 or 73 times respectively lower than that obtained with an injection of 99mTc-MAG3. All organs except kidneys would receive an estimated effective absorbed dose of <0.1 μSv/MBq for 18F-PFH or 124I-OIH. Kidneys would receive a dose of 0.83 or 0.77 μSv/MBq respectively for 18F-PFH or 124I-OIH. Conclusions: Our results indicate that 18F-PFH and 124I-OIH would deliver much safer levels and lower radiation doses to the patients compared to 99mTc-MAG3 and warrants a clinical trial to estimate the radiation doses more accurately.
Keywords: para-18F-fluorohippurate